Effect of moderate and Severe Hypoxic exposure coupled with fatigue on psychomotor vigilance testing, muscle tissue oxygenation, and muscular performance - Smith, C. M.; Salmon, O. F.; Jenkins, J. R. (Current Research in Physiology, 2021)
• Moderate Hypoxia (FiO2: 15.4%) coupled with fatigue resulted in a decrease in reaction time. • Severe Hypoxia (FiO2: 12.9%) coupled with fatigue resulted in increased error rate and a decrease in reaction time. • Fatigue was the primary influencer on heart rate, muscular strength, and muscular endurance and not hypoxic exposure. • Severe Hypoxia (FiO2: 12.9%) resulted in greatly reduced muscle tissue oxygenation saturation before and after fatigue.